Landscape and land use affect composition and nutritional values of bees’ food - Inês da Silva, Cláudia; Victorino Nicolosi Arena, Mariana; Cristina Mathias da Silva, Elaine; Roberto Martines, Marcos; Malaspina, Osmar [UNESP]; Chiovatto, Giovani [UNESP]; de Melo Nascimento, José Elton; Tadei, Rafaela [UNESP]; Hartung Toppa, Rogério (Elsevier, 2024)
Bees are primary pollinators across various terrestrial biomes and rely heavily on floral resources for sustenance. The composition of landscapes can influence bee foraging behavior, while human activities can directly affect both the composition and nutritional value of bee food. We aimed to assess how landscape structure and land use practices can impact the composition and nutritional value of food sources for two generalist social bee species, Apis mellifera and Scaptotrigona postica. Food samples were collected from twenty-five colonies of A. mellifera and thirteen of S. postica to examine how food composition and nutritional value may vary based on the extent of human land use and the composition of landscapes surrounding beekeeping sites. The pollen composition and nutritional value of A. mellifera were influenced by both land use practices and landscape heterogeneity. The number of patches determined total sugar and lipid content. Landscape heterogeneity affected pollen composition in S. postica, primarily due to the number of patches, while total sugar was affected by landscape diversity. Pollen nutritional value in S. postica was linked to land use, mainly meadow and vegetation, which influenced total sugar and dry matter. S. postica showed a higher sensitivity to land use changes compared to A. mellifera, which was more affected by landscape heterogeneity. Assuring landscape heterogeneity by preserving remaining forest patches around apiaries and meliponaries is crucial. Thoughtful land use planning is essential to support beekeeping activities and ensure an adequate quantity and quality of bee food resources.
Keywords: Apis mellifera; Ecological resources; Pollinators; Scaptotrigona postica; Spatial heterogeneity; Trophic niche